Up in the Air: How Airlines Can Improve Performance by Engaging their Employees - Gould, Anthony M. (Relations industrielles / Industrial Relations, 2009)
Up in the Air: How Airlines Can Improve Performance by Engaging their Employees, by Greg J. Bamber, Jody H. Gittell, Thomas A. Kochan and Andrew Von Nordenflycht, is reviewed.
Keywords: Airline industry; Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Deregulation; International; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Strategic management